Meningkatkan Keterampilan Proses Sains Pada Pembelajaran Fisika Menggunakan Metode Percobaan Pada Siswa Kelas X MS 5 SMA Negeri 2 Banjarmasin - Hidayah, Nurul; Arifuddin, Muhammad; Mahardika, Andi Ichsan (Berkala Ilmiah Pendidikan Fisika, 2017)
During this time of learning in school are still conventional, so it causes the studentsâ sciences process kills. To that end made efforts to improve sciences process skills using the experiment methods that has a specific purpose describe; (1) the feasibility RPP through the experiment methodsÂ  (2) the students sciences process skills through the experiment methods and (3) student learning outcomes after the implementation the experiment methods. This type of research is a classroom action research using the Kemmis & Taggart model design. Data collection techniques such as observation, assessment, tests and documentation. Descriptive data analysis techniques such as qualitative and quantitative. results showed: (1) feasibility RPP reached done very well, (2) increased The studentsâ sciences process skills with good category, (3) improved student learning outcomes with classical completeness amounted to 86.21%. So it can Â concluded that the experiment methods can improving students sciences process skills class X MS 5 SMA Negeri 2 Banjarmasin.